Achieving Energy Cost Saving Using Best Energy Tariff: A Case Study Of A Sewage Plant - Sukri, Mohamad Firdaus; Mohd Tahir, Musthafah; Ab Razak, Juhari; Ab Rahman, Azhan (Praise Worthy Prize, 2021)
Understanding the energy cost tariffs or the models of commercial and industrial sectors is a crucial topic due to the high energy costs and its significant cost saving potentials. This paper has investigated the potential of the electrical energy cost saving using different energy cost tariffs of a commercial sewage plant in Malaysia. The current energy tariff of B (Low Voltage Commercial) has been compared to four other possible energy tariffs. The actual electricity consumption of 2019 has been used as baseline data. It has been found out that at lower electricity consumption, energy tariff of D (Low Voltage Industrial (with discount)) has the greatest potential of energy cost saving compared to other tariffs. The superiority of this tariff leads to the highest cumulative energy cost saving. Based on the current and future projection of electricity consumption, it is proposed that the sewage plant switches its energy tariff to D (Low Voltage Industrial). Once approved, it is suggested to apply for a further 10% of energy cost saving through the special tariff of D (Low Voltage Industrial (with discount))